Effect of Genetic Material and Rotation on the Properties of Charcoal - Romanelli, João Paulo; Gonçalves, Maria Carolina Pereira; Costa, Mayara F; Carvalho, Ana Márcia Macedo Ladeira (Ciência e Natura, 2018)
This study aimed to evaluate chemical properties and yield of charcoal from two Eucalyptus urophylla clones considering the first and second rotation of the wood. The study was carried out with material from Arcelor Mittal Jequitinhonha, with a mean age of 61.5 months. The values of fixed carbon, volatile materials, ash content, higher calorific value, gravimetric yield, liquid yield and gas yield were determined. The data were analyzed statistically by Analysis of Variance (ANOVA) and significant differences were compared by the Tukey test (p <0.05). The results showed significant differences for the fixed carbon contents (67% and 70.5%) and volatile materials (32% and 29%) of clones AEC 0182 and AEC 0296, respectively. The analysis of the results showed that both the first and second rotation woods have satisfactory characteristics for charcoal production and are not influenced by the effect of the rotations.